Chronic Active Epstein-Barr Virus Infection With Central Nervous System Involvement in Children: A Clinical Study of 22 Cases. Issue 1 (11th October 2022) - Ou, Wenxin; Zhao, Yunze; Wei, Ang; Ma, Honghao; Zhang, Liping; Lian, Hongyun; Zhang, Qing; Chen, Sitong; Wang, Dong; Li, Zhigang; Wang, Tianyou; Zhang, Rui
Abstract : Objective: To analyze the clinical features, treatment, and prognosis of chronic active Epstein-Barr virus infection (CAEBV) with central nervous system (CNS) involvement in children. Methods: Patients with CAEBV admitted to Beijing Children's Hospital, Capital Medical University, were enrolled in this study from January 2017 to December 2020. They were divided into a CNS group and a non-CNS group based on the presence of CNS involvement. Results: Twenty-two patients developed CNS disease, accounting for 23.9% (22/92) of CAEBV patients in the same period. Of these, only 2 of 22 patients presented initially with neurologic symptoms in the CNS group, and they all improved after treatment. Cerebrospinal fluid (CSF) examination demonstrated normal protein concentration and cell number in all patients with CNS involvement. Only 7 patients were positive for CSF EBV-DNA. Twenty-one patients had neuroimaging abnormalities, such as white matter signal abnormalities, encephalography or calcification. In the CNS group, 7 (31.8%) patients died, including 5 who died of active hemophagocytic lymphohistiocytosis, 1 died of unrelated causes, and 1 died of respiratory failure caused by pulmonary lymphoproliferative disease progression after transplantation. The 3-year overall survival was lower in the CNS group than in the non-CNS group (63.6% ± 11.9% versus 86.9% ± 4.1%, P = 0.027). Hemophagocytic lymphohistiocytosis (HLH) is an independent risk factor for CNS involvement in patients with CAEBV (OR = 2.946, 95% CI: 1.042–8.335, P = 0.042). Compared with the non-CNS group, blood EBV-DNA loads and CD4+/CD8+ ratio of T lymphocytes in the CNS group were higher ( P < 0.001), while fibrinogen levels and natural killer (NK)-cell activity were lower ( P = 0.047). Children with CAEBV were more likely to develop CNS diseases with low NK-cell activity (NK-cell activity < 14.00%, P = 0.023) or high alanine aminotransferase (ALT) levels (ALT levels > 40 U/L, P = 0.032). Conclusion: CAEBV with CNS involvement has nonspecific clinical manifestations, laboratory data, neuroimaging but has a worse prognosis. Blood fibrinogen levels and NK-cell activity in CAEBV children with CNS involvement are lower than in those without CNS involvement. In contrast, blood EBV-DNA loads and CD4+/CD8+ ratio of T lymphocytes are higher. Children with CAEBV who presented with HLH, NK-cell activity <14.00%, serum ALT >40 U/L and high-blood EBV-DNA loads are prone to develop CNS diseases.